Assessment of three-dimensional RC moment-resisting frames under repeated earthquakes. (August 2020) - Oggu, Praveen; Gopikrishna, K.
Abstract: Earthquakes are one of the major unavoidable natural disasters. These are characterized by the recorded ground motion data at a particular location. In any real earthquake event, shaking repeatedly occur several times within a few hours or days. In view of lack of time between the occurrences of tremors, the rehabilitation of the structure often becomes impractical, and the structural damages get accumulated. Hence, it is imperative to assess the behavior of reinforced concrete (RC) buildings under repeated earthquakes to prevent a disaster. The current practices of earthquake-resistant design utilize only a single strongest earthquake input in the form of a response spectrum, corresponding to the seismic code of practice at the site location. Hence, this investigation is primarily focused on vulnerability assessment of three-dimensional RC building frames conformed to the Indian standard codes of practice under bi-directional single and repeated ground motions. Incremental dynamic analysis is carried out to assess the inelastic behavior of the structure in terms of maximum horizontal displacement, residual displacement, and maximum inter-story drift ratio for particular spectral accelerations. The results obtained in this investigation conclude that the collapse capacity of RC building under repeated earthquakes reduces significantly compared to that of the most severe single earthquake. This emphasizes the need to account for repeated earthquake forces during the design phase in order to build a seismic resilient structure.